Hubungan Sumber Informasi Kesehatan Reproduksi Terhadap Kejadian Perilaku Seksual Beresiko Pada Remaja di Desa sukolilo kecamatan Wajak - Namirotuz Zakiyyah; L. Ajeng Wijayanti; Sri Rahau Rahayu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Introduction: information is a factor that influences the formation of a person's behavior. In this case. The existence of new information about sex in adolescents provides a new knowledge base for the formation of sexual behavior in adolescents.This study aims to analyze the relationship between sources of information on KRR and dangerous sexual behavior in adolescents in Sukolilo Village, Wajak District. This research is an analytic study with a cross-sectional approach. Methods: The research sample is 90 people with Quota sampling technique. Results: Based on the Spearman Rank correlation test, the relationship between sources of reproductive health information and risky sexual behavior in adolescents obtained P value = 0.106, which is greater than the significant level (α) 0.05, the results show that there is no significant relationship between sources of reproductive health information. with the incidence of risky sexual behavior in adolescents in the village of Sukolilo, Wajak sub-district. Discussion: In this study, it is necessary to conduct further studies on the factors causing risky sexual behavior in adolescents, including knowledge, attitudes of involvement in educating adolescent sex behavior and the involvement of adolescents themselves in giving more attention to themselves and self-control in order to avoid sexual dangerous behavior.